(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Reducing emissions global economies demands the development of "green technology," which entails a reorganization of the energy sector to use renewable energy sources and nitrogen transportation systems. This reconstruction will need massive quantities of raw materials, some of which are in short supply. A unique method for spotting potential drawbacks of future demand versus geophysical supply is proposed to assess potential risks. This was applied to the international development of wind electricity, photovoltaic power electricity, solar thermal electricity, and passenger electric transportation from 2016 to 2050 under a marketing scenario, keeping in mind the influence on 31 raw material. As a result, 13 factors have been recognized as having a very high or high risk of causing future blockages: chromium, chromium, cobalt, bronze, gallium, indium, lithium, manganese, nickel, silver, tellurium, tin, and zinc. The most dangerous group is tellurium, which is used to manufacture solar photovoltaic cells. To overcome these restraints, initiatives aimed at boosting resource utilization from 0.1% to 4.6% per year may be able to circumvent material shortages and green technology restraints. In 2050, the lithium load factor, for example, would increase from 1% to 4.8 percent. This study aims will prepare the students for developing eco design and composting techniques.